Engaging Stakeholders in the Development of a Reproductive Goals Decision AID for Women with Cystic Fibrosis. (February 2022) - Stransky, Olivia M.; Pam, Molly; Ladores, Sigrid L.; Birru Talabi, Mehret; Borrero, Sonya; Godfrey, Emily M.; Roe, Andrea H.; Sawicki, Gregory S.; Zuckerwise, Lisa C.; Mody, Sheila; Mentch, Laura; Deal, Ashley; et al.
Objective : More people with cystic fibrosis (pwCF) are reaching adulthood and considering their reproductive futures. Unfortunately, many pwCF report gaps in their reproductive healthcare. We describe measures of stakeholder engagement in developing a reproductive goals decision aid for women with CF called MyVoice:CF .Methods: Stakeholders reviewed the content, design, and usability of the tool, which was informed by prior research related to CF family planning experiences and preferences as well as a conceptual understanding of reproductive decision making. We evaluated stakeholder engagement via process measures and outcomes of stakeholder involvement. We collected data via recorded stakeholder recommendations and surveys.Results: Fourteen stakeholders participated and the majority described their role on the project as "collaborator", "advisor", or "expert." Most felt their expectations for the project were met or exceeded, that they had contributed significantly, and that they received sufficient and frequent information about the process. All stakeholders provided recommendations and clarified aims for a CF-specific family planning tool, including its content and focus on facilitating shared decision making.Discussion: Utilizing meaningful stakeholder contributions, we developed MyVoice:CF, a novel web-based decision aid to help women with CF engage in shared decision-making regarding their reproductive goals.Practical Value: Our findings from working with stakeholders for MyVoice:CF indicate that disease-specific reproductive health resources can and should be designed with input from individuals in the relevant communities.